Relationships between participation in recreational activities and leadership behavior: a study on the secondary school students - Umut Basoglu (Türk Spor ve Egzersiz Dergisi)
Recreation is defined as the optional and voluntary activities that are carried out individually or in a team inleisure times other than obligatory ones, and that give satisfaction to the individuals, by eliminating the adverseeffects of the industrial society. As is seen, recreation becomes a dynamic lifestyle and culture element whichremains widespread in the modern society. Emphasizing the concept of recreation and its important role onpersonal development in general on leadership attitudes in particular, it is aimed to reveal the effects of theparticipation of the secondary students in the recreational activities on the leadership attitudes. To reach thisend, a survey is conducted on 289 secondary school's students in Istanbul, Bursa and Izmir. Data is submitted tofactor, frequencies, reliability and ANOVA analyses through SPSS 13.0 demo version. The findings reveal thatstudents who are engaging in sports activities have higher scores on transformational leadership traits whilestudents who are not engaging such activities mainly exhibit transactional leadership behaviors. Moreover, thefindings reveal that the scores for both transformational and transactional leadership behaviors of students whoare engaging sports activities are higher than the scores of students who are not carrying out these activities.The results underline the fact that participation in sports activities as recreational activities plays an importantrole on the development of leadership attitudes for secondary school students.